Embryonic stem cell transplantation: potential applicability in cell replacement therapy and regenerative medicine. - Wu, D; Boyd, A; Wood, K (2007)
Embryonic stem cells are derived from the inner cell mass of the trophoblast, and have the ability to differentiate into all the tissues of the fetus. As such, their potential in cell replacement therapy and regenerative medicine has been widely acknowledged. Useful cell types such as neurons, cardiomyocytes, hepatocytes, pancreatic beta cells, and blood cells have all been successfully derived in the laboratory. Furthermore, embryonic stem cells may be utilized in novel immunomodulatory applications, such as hematopoietic chimerism strategies aimed at inducing tolerance to donor organ allografts. Unfortunately, progress in embryonic stem cell therapeutics continues to be hindered by haphazard differentiation and tumorigenesis; and the immune response to an embryonic stem cell-derived tissue graft is still an open question. This review summarizes the current state of embryonic stem cell research in regards to transplantation, highlighting the successes to date and the future obstacles yet to be overcome. Although embryonic stem cells are still far from their debut in the clinic, continued scientific advances engender optimism that they will eventually play an important role in cell replacement therapy and regenerative medicine.